The impact of COVID‐19 on thoracic surgery residency programs in the US: A program director survey - Coyan, Garrett N. (J Card Surg, 2020)
OBJECTIVE: The coronavirus disease 2019 (COVID‐19) has altered how the current generation of thoracic surgery residents are being trained. The aim of this survey was to determine how thoracic surgery program directors (PDs) are adapting to educating residents during the COVID‐19 pandemic. METHODS: Thoracic surgery PDs of integrated, traditional (2 or 3 year), and combined 4 + 3 general/thoracic surgery training programs in the United States were surveyed between 17th April and 1st May 2020 during the peak of the COVID‐19 pandemic in much of the United States. The 15‐question electronic survey queried program status, changes to the baseline surgical practice, changes to didactic education, deployment/scheduling of residents, and effect of the pandemic on case logs and preparedness for resident graduation. RESULTS: All 23 institutions responding had ceased elective procedures, and most had switched to telemedicine clinic visits. Online virtual didactic sessions were implemented by 91% of programs, with most (69.6%) observing same or increased attendance. PDs reported that 82.7% of residents were on a non‐standard schedule, with most being deployed in a 1 to 2 week on, 1 to 2 week off block schedule. Case volumes were affected for both junior and graduating trainees, but a majority of PDs report that graduating residents will graduate on time without perceived negative effect on first career/fellowship position. CONCLUSIONS: The COVID‐19 pandemic has radically changed the educational approach of thoracic surgery programs. PDs are adapting educational delivery to optimize training and safety during the pandemic. Long‐term effects remain uncertain and require additional study.